Performance-Index Based Rule Engine for Improving Routing Performance of a Tactical Network - Yoon, Daegun; Roh, Byeong Hee; Oh, Sangyoon (Journal of Korean Institute of Communications and Information Sciences, 2022)
The scale of data generated from the military operations as well as the demand of processing the large-scale data are increasing. A military network is comprised of diverse devices from different vendors. Thus, a software-defined network (SDN) is proposed to make the network management simple regardless of device vendors. In this study, we design a rule engine that enhances the performance of packet transmission in SDN environment. The rule engine includes an algorithm that modifies a routing path of each flow in flow table, and determines whether the performance is improved or not by looking at the overall performance index. For future works, we adopt the rule engine in real network environment to improve the network performance.
Keywords: routing performance; rule engine; Software-defined network